PREDIKSI ALIRAN LAHAR GUNUNG API MENGGUNAKAN PEMODELAN SPASIAL DINAMIS STUDI KASUS LETUSAN GUNUNG GALUNGGUNG TAHUN 1982 - NUGROHO, HARY
Geologically, the Indonesia Archipelago is situated in the intersection of three tectonic plates. At the subduction of those plates, lies approximately 500 volcanoes, of which 129 can be considered active. The danger to life posed by active volcanoes is not limited to the activities during the eruption such as pryoclastic flow, eruption of molten rock, showers of ash and cinders, or other disasters which are different from one mountain to another. Disastrous mudflows, as a posteruption occurences, are an equally serious hazard. The advancement of Geographical Information System (GIS) and the availability of Digital Terrain Model (DTM) with even higher accuracy give the alternative to the utilization of GIS in predicting and monitoring the impact of one volcanic eruption to the surrounding area. This thesis attempts to develop a model of lahar flow using GIS and DTM to predict the danger zone overwhelmed by the lahar. The method used for the modelling is Dynamic Spatial Modelling, and the model itself put an emphasize at the course of the lahar flow, the topography of the terrain, and the velocity of the flow. The subject area is Gunung Galunggung at the 1982 eruption. The result of this research shows that danger zone predicted by the model matches the real condition as mapped by the Directorate of Vulcanology.